Understanding torture : law, violence, and political identity - Parry, John T., 1964- (University of Michigan Press, 2010)
Prohibiting torture will not end it. In Understanding Torture, John T. Parry explains that torture is already a normal part of the state coercive apparatus. Torture is about dominating the victim for a variety of purposes, including public order; control of racial, ethnic, and religious minorities; and -- critically -- domination for the sake of domination. Seen in this way, Abu Ghraib sits on a continuum with contemporary police violence in U.S. cities; violent repression of racial minorities throughout U.S. history; and the exercise of power in a variety of political, social, and interpersonal contacts. Creating a separate category for an intentionally narrow set of practices labeled and banned as torture, Parry argues, serves to normalize and legitimate the remaining practices that are "not torture." Consequently, we must question the hope that law can play an important role in regulating state violence. -- Publisher description